HPTLC Determination of Gallic Acid in Crude Drugs and Herbal Formulations - Ahmad, S.; Kamal, Y.T.; Singh, M.; Parveen, Rabea; Mohamed Musthaba, S. (Asian Journal of Chemistry, 2010)
A simple, selective, precise, accurate and cost effective high performance thin layer chromatographic (HPTLC) method for the analysis of gallic acid in some herbal formulations have been developed and validated. Aluminium TLC plate precoated with silica gel 60F254 was used as the stationary phase whereas ethyl acetate:formic acid (8.5:1.1, v/v) was used as the mobile phase. A compact and well resolved peak of gallic acid was observed by densitometric analysis in the absorbance mode at 272 nm. Calibration curve revealed a good linear relationship between the peak area and concentration. Validation of the developed method also carried out and found to be accurate, precise, specific and reproducible. The method proposed was further applied for estimation of gallic acid in the hydrolyzed samples of three Ayurvedic tablet formulations viz., amla, haritaki and triphala. Hence, newly developed and validated HPTLC method for quantification of gallic acid may be useful in quality control and standardization of several herbal formulations and crude drugs containing phenolics and tannins.